2021
DOI: 10.3390/su132212468
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Sport Education Model-Based Teaching Intervention on Students’ Behavioral and Motivational Outcomes within the Physical Education Setting in the COVID-19 Scenario

Abstract: The sport education model (SEM) has been suggested to have a positive impact on students’ motivational processes within the physical education setting. However, there is no evidence about how this methodology can affect such processes in the unconventional scenario provoked by the COVID-19 pandemic. The aim of the present study was to analyze the effect of a SEM-based teaching intervention on students’ basic psychological needs (BPN), intrinsic motivation, and behavioral engagement in physical education. For t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 65 publications
2
8
0
Order By: Relevance
“…Regarding BPN satisfaction, which had a medium effect size in terms of effects of the intervention, the present study findings align with the results from previous interventions carried out within the PE context, which have been successful in improving students’ BPN satisfaction [ 4 , 34 , 37 , 41 ]. According to the literature, students’ BPN satisfaction can be fostered through the implementation of interventions specifically designed to create motivational contexts [ 31 , 32 , 41 ] or through model-based experiences [ 34 , 35 , 38 , 39 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Regarding BPN satisfaction, which had a medium effect size in terms of effects of the intervention, the present study findings align with the results from previous interventions carried out within the PE context, which have been successful in improving students’ BPN satisfaction [ 4 , 34 , 37 , 41 ]. According to the literature, students’ BPN satisfaction can be fostered through the implementation of interventions specifically designed to create motivational contexts [ 31 , 32 , 41 ] or through model-based experiences [ 34 , 35 , 38 , 39 ].…”
Section: Discussionsupporting
confidence: 89%
“…Unsurprisingly, both motivational and behavioural processes among students in the PE setting are likely to be affected by interactions happening in class [ 31 , 32 ]. In this regard, the use of certain methods in which the focus has shifted from the teacher and instruction to the student and learning have been found to be associated with more-adaptive motivational regulations [ 33 , 34 , 35 ] and with higher engagement [ 36 ] in PE. More specifically, there are certain specific methodological approaches that have been suggested to be successful in the creation of adaptive contexts.…”
Section: Introductionmentioning
confidence: 99%
“…240 2021), mainly due to social differences and vulnerability into these countries. From this, the confirmatory scientific reports can lead and reinforce new political procedures to improve the public health services, teaching methods, lifestyle, sports and physical activity for children and adolescents to reach a better level of mental and physical well-being and HQOL (Franco et al, 2021). Thus, understanding the associations between physical activity and HQOL could guide the development of strategies for health promotion in children and adolescents.…”
Section: Lemes Et Almentioning
confidence: 90%
“…Finally, in (Franco et al, 2021) was carried out in Spain during the pandemic considering 50 participants aged between 14 − 15 years, in which they were divided into 2 groups (control group and intervention group). A survey was done, the questions were asked as an incentive.…”
Section: ____________________________________________________________...mentioning
confidence: 99%
“…Most people forced to stay at home or adopt isolation protocols to prevent transmission of the virus (Tel, 2021). For this purpose, multiple exercise modes can be applied in home, including aerobic exercise using stationary bikes or rowing ergometers, body-weight training, dance exercise and active gaming (Hammami et al, 2020), but not everyone has this equipment at home. Therefore, some pandemic studies indicated that technology could help in the practice of PA without having it present (Okmawati, 2020).…”
Section: Introductionmentioning
confidence: 99%